The impact of crisis on spatial structure of the Network Company - Syssoeva, Natalia M.; Sadovsky, Pavel A. (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
The paper presents changes in the spatial relationships between the agents of the network company in times of crisis. The analyzed company performs the production and supply of cement-based and polymer materials for industrial construction and has offices in the most industrialized regions of Russia. In crisis the company decided to withdraw from certain markets and closed some regional missions. The rupture of a unitary structure of the company led to formation of separate regional firms. On the basis of the parent company new organizations have been formed in some regions united by a common client base, similar products and a unified social network. This process has both positive and negative aspects for customers and manufacturers. The need for policy coherence for the overall survival results in the formation of a new regional industry clusters with the intention of improving product and service quality.